Alien Pathogens on the Horizon: Opportunities for Predicting their Threat to Wildlife. Issue 4 (4th October 2016) - Roy, Helen E.; Hesketh, Helen; Purse, Bethan V.; Eilenberg, Jørgen; Santini, Alberto; Scalera, Riccardo; Stentiford, Grant D.; Adriaens, Tim; Bacela‐Spychalska, Karolina; Bass, David; Beckmann, Katie M.; Bessell, Paul; et al.
Abstract: According to the Convention on Biological Diversity, by 2020 invasive alien species (IAS) should be identified and their impacts assessed, so that species can be prioritized for implementation of appropriate control strategies and measures put in place to manage invasion pathways. For one quarter of the IAS listed as the "100 of the world's worst" environmental impacts are linked to diseases of wildlife (undomesticated plants and animals). Moreover, IAS are a significant source of "pathogen pollution" defined as the human‐mediated introduction of a pathogen to a new host or region. Despite this, little is known about the biology of alien pathogens and their biodiversity impacts after introduction into new regions. We argue that the threats posed by alien pathogens to endangered species, ecosystems, and ecosystem services should receive greater attention through legislation, policy, and management. We identify 10 key areas for research and action, including those relevant to the processes of introduction and establishment of an alien pathogen and to prediction of the spread and associated impact of an alien pathogen on native biota and ecosystems. The development of interdisciplinary capacity, expertise, and coordination to identify and manage threats was seen as critical to address knowledge gaps.